Steamboat PROSPECTOR on the Yukon River, Yukon Territory, 1901. - University of Washington Libraries. Special Collections Division
PH Coll 246.186 [Meed journal: "Steamer "Prospector," on trial trip. Captain James A. Ritchie in command."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number